The influence of unemployment upon the masculinities of Chinese-Singaporean male and married professionals, managers and executives - Wina (2015)
The research seeks to study the influence of unemployment upon the masculinities of the Chinese-Singaporeans Male and married Professionals, Managers and Executives (CSMPME) in the context of dual-earner families. The study uses a sociological framework combining Raewyn Connell’s concept of Hegemonic Masculinity and Pierre Bourdieu’s Theory of Practice (habitus, capitals and fields). Masculinities refer to the practices of socially constructed male bodies in differing circumstances. The findings revealed that CSMPME varied in their definitions of masculinities with the three main qualities being that of an economic provider, a professional worker and being a contributor which were all constructed around paid employment. Social stigma associated with unemployment affected the masculinities of some CSMPME and lowered their social status both in the family and society. Although CSMPME tried to negotiate their degraded social status, they faced the dilemma in choosing between maintaining and changing their masculinities to adapt to their degraded social status.